2017
DOI: 10.1002/cphc.201700650
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Base‐Stable Metal–Organic Frameworks for Selective CO2 Adsorption and Proton Conduction

Abstract: Metal–organic frameworks (MOFs) have shown great potential for application in various fields, including CO2 capture and proton conduction. For promoting their practical applications, both optimization of a given property and enhancement of chemical stability are crucial. In this work, three base‐stable isostructural MOFs, [Ni8(OH)4(H2O)2(BDP‐X)6] (Ni–BDP‐X; H2BDP=1,4‐bis(4‐pyrazolyl)benzene, X=CHO, CN, COOH) with different functional groups, are designed, synthesized, and used in CO2 capture and proton conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…However,s ome peaks from 9.5 to 258 slightly shift towardlower anglesc ompared with the simulated ones, which showsa ne xpansion of the lattice after absorption of water molecules. Thus, it leads to the optimized protonconductivity for 1 of 1.50 10 À3 Scm À1 .A sl isted in Ta ble 2, althought he optimized conductivity value is smaller than that of severalr ecent MOFs, [38][39][40][41] this value can be compared to that of some previousM OFs under similar tested conditions, [41][42][43][44][45][46] and is remarkably highert han that of four imidazole dicarboxylate-based Co II MOFs and other MOFs. [27,28,47] It is illustrated again that the structural advantage of MOF 1 is the a large amount of uncoordinated carboxylate units between the layers forprotontransfer.…”
Section: As Shown Inmentioning
confidence: 76%
See 1 more Smart Citation
“…However,s ome peaks from 9.5 to 258 slightly shift towardlower anglesc ompared with the simulated ones, which showsa ne xpansion of the lattice after absorption of water molecules. Thus, it leads to the optimized protonconductivity for 1 of 1.50 10 À3 Scm À1 .A sl isted in Ta ble 2, althought he optimized conductivity value is smaller than that of severalr ecent MOFs, [38][39][40][41] this value can be compared to that of some previousM OFs under similar tested conditions, [41][42][43][44][45][46] and is remarkably highert han that of four imidazole dicarboxylate-based Co II MOFs and other MOFs. [27,28,47] It is illustrated again that the structural advantage of MOF 1 is the a large amount of uncoordinated carboxylate units between the layers forprotontransfer.…”
Section: As Shown Inmentioning
confidence: 76%
“…[Also, 53 %R H: from 1.10 10 À6 Scm À1 (at 70 8C) to 3.41 10 À5 Scm À1 (at 100 8C; Figure S6 bi nt he Supporting Information);6 8% RH:f rom 2.81 10 À7 Scm À1 (at 25 8C) to 4.61 10 À4 Scm À1 (at 100 8C; Figure S7 in the SupportingI nformation); 75 %R H: from 6.37 10 À7 Scm À1 (at 25 8C) to 5.71 10 À4 Scm À1 (at 100 8C; Figure S8 in the SupportingI nformation); 85 %R H: from 1.12 10 À6 Scm À1 (at 25 8C) to 1.14 10 À3 Scm À1 (at 100 8C; Figure S9 in the SupportingI nformation); 93 %R H: from4 . 45 10 À6 Scm À1 (at 25 8C) to 1.14 10 À3 Scm À1 (at 100 8C; Figure S10 in the Supporting Information);9 8% RH:f rom 1.48 10 À5 Scm À1 (at 25 8C) to 1.51 10 À3 Scm À1 (at 100 8C; Figure 3b)]. I ts hould be stressed that the conductivity values at high temperature (or high RH) are one to three orders of magnitude larger than those at low temperature (or lowR H) under the same RH (or the same temperature), which is typical proton conduction behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Through a large amount of research, it has been found that the proton conductivities of MOFs can be regulated by introducing different components, such as acidic moieties (e.g.,R SO 3 H, H 3 PO 4 ) and extraneous protonic molecules (e.g.,a mine, N-heterocy-cles), into the pores and channels of MOFs. [8,17,18,[25][26][27][28][29][30] Stimulated by this, we hope to apply proton-conductiveM OFs to the sensing of alkaline or acidic gases. Fortunately,w ehave successfully deployed several proton-conductive MOFs as reliable NH 3 sensors.…”
Section: Introductionmentioning
confidence: 88%
“…Meanwhile, MOFs have been evaluated as promising candidates as new types of crystalline proton‐conducting materials. Through a large amount of research, it has been found that the proton conductivities of MOFs can be regulated by introducing different components, such as acidic moieties (e.g., RSO 3 H, H 3 PO 4 ) and extraneous protonic molecules (e.g., amine, N‐heterocycles), into the pores and channels of MOFs . Stimulated by this, we hope to apply proton‐conductive MOFs to the sensing of alkaline or acidic gases.…”
Section: Introductionmentioning
confidence: 99%
“…The MOF showed a moderate porosity with a BET surface area of 576 m 2 g −1 and a pore volume of 0.37 cm 3 g −1 . Like many other stable metal bipyrazolate MOFs, Cu‐tebpz was proven stable in boiling solvent (THF, toluene, hexane, or DMSO), water, and even acidic (1 × 10 −3 m HCl) and basic (1 × 10 −3 m NaOH) aqueous solutions for 24 h by PXRD patterns. The hydrophobicity of Cu‐tebpz was confirmed by its water adsorption isotherm, which showed almost negligible uptakes, even at high humidity up to 0.9 P / P 0 at 298 K, but an abundance of benzene and n‐hexane could be adsorbed by the MOF under the same conditions.…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 96%